Images of the Orient by three female writers in the 19th century, Amalia Nizzoli, Ida Pfeiffer and Isabelle Eberhardt - (:unkn) unknown (My University, 2018)
The thesis focuses on the travel writings of three European women who travelled to the Middle East and to North Africa in the 19th century. Two of them, Ida Pfeiffer (1797) and Amalia Nizzoli (1806) came from the Austro-Hungarian Empire and travelled in the Middle-East controlled by the Ottoman Empire. Isabelle Eberhardt (1877) travelled in the North African countries controlled by the French colonial power. By comparing the narrations of the three writers of the oriental landscapes and their inhabitants with a special attention for the oriental women, the thesis questions whether being a woman affects their vision of the Orient. Starting point is Edward Saïd’s thesis of Orientalism, that is to say of the image of the East created by the West on the basis of a binary point of view according to which the two cultures are opposed to each other and the East is described as inferior to the West.like in the descriptions of Isabelle Eberhardt of some regions subdued to the control by the West
Keywords: African Research